Effect of Functional Threshold Trainings Applied to Junior Elite Cyclists on Power and Strength Parameters - Duran Akbaş; Fatih Kılınç (Türk Spor ve Egzersiz Dergisi)
The aim of the study is to examine the effect of functional threshold power training applied to young elite cyclists on power and strength parameters. 24 young elite level cyclists participated voluntarily. In our study, it was divided into two groups as Functional threshold training group (FTTG) and Traditional training group (TTG). Functional threshold training group n:12 (age 17 years, height 1,73±8,5 m., body weight 64,87±10.4 kg. and sports age 4,6±1.3), Traditional training group) n:12 (age 17 years, height 1,73±8,81 m., body weight 58,8±9,1 kg. and sports age 4,1 years). 30 sec Anaerobic power test, 20 min FTP test, 40 km. endurance and strength tests were applied to both groups as pre-post test. The obtained data were compared using the within-group Paired T test and the between-group Independent T test in the IBM SPSS Statistics 24.0 program. Traditional training group; Anaerobic power, 20 min FTP aerobics power, 40 km. endurance and strength pre-post test values improved. Functional threshold training group; Anaerobic power, 20 min FTP aerobic power, 40 km. endurance and strength pre-post test values were found to be more effective training development p<0.05. In spite of the performance improvement in both groups of athletes participating in the study, FTP training group showed more progress. Based on the data we obtained, cycling and strength training can be an example for trainers and sports scientists working on cycling.